How to read a painting : lessons from the old masters - Rynck, Patrick de, 1963- (New York : H.N. Abrams, 2004)
This book decodes the imagery of more than 150 of the most influential and admired artworks of all time.
From Duccio Di Buoninsegna (about 1255-1319) to Francisco de Goya (1746-1828).
Includes bibliographical references (p. 364-367) and index.
Keywords: Painting, European -- Themes, motives; Painting -- Appreciation; Symbolism in art